2018
DOI: 10.1002/jcb.28177
|View full text |Cite
|
Sign up to set email alerts
|

A new method for excavating feature lncRNA in lung adenocarcinoma based on pathway crosstalk analysis

Abstract: Recent theoretical and experimental studies indicate that long-chain noncoding RNAs (lncRNAs) are essential for the growth and differentiation of cells and the occurrence and development of tumors in epigenetics, but the regulation of lncRNA on gene expression, transcriptional activation, and transcriptional interference in diseases is still unclear. There is an urgent need for effective methods to discover significant lncRNAs with their functions on gene regulatory mechanisms. For this purpose, a new method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 48 publications
(99 reference statements)
1
22
0
Order By: Relevance
“…Cell cycle dysfunction in LUAD was consistent with our results. A recent study demonstrated that cell cycle-related genes, such as E2F1 (Chen et al, 2019), were enriched during the regulation of the cell cycle progression (Li et al, 2018;Qi et al, 2019). In the present study, we found that lncRNA RAET1K could promote cell cycle dysfunction, providing insight into the crosstalk regulatory mechanism between lncRNAs and coding genes.…”
Section: Discussionsupporting
confidence: 62%
“…Cell cycle dysfunction in LUAD was consistent with our results. A recent study demonstrated that cell cycle-related genes, such as E2F1 (Chen et al, 2019), were enriched during the regulation of the cell cycle progression (Li et al, 2018;Qi et al, 2019). In the present study, we found that lncRNA RAET1K could promote cell cycle dysfunction, providing insight into the crosstalk regulatory mechanism between lncRNAs and coding genes.…”
Section: Discussionsupporting
confidence: 62%
“…WGCNA analysis was performed based on the 857 genes to identify gene co-expression networks and their underlying clinical significances. WGCNA is a system-level method for identifying modules of highly correlated genes from microarray or RNA-seq datasets and for relating modules to clinical traits 29 , which has been applied in various biological contexts, including cancer 30,31 . In this study, we identified three modules of the 857 genes by using the WGCNA approach, among which MEturquoise with 423 genes showed close links with the survival time, pathology grade and TNM stage of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies exploring lncPVT1's clinical application. The results reveal that lncPVT1 is a potential biomarker for some tumors as its expression is abnormal and the detecting technology has been optimized (6266). And as a more stable form, circPVT1 may be more valuable in clinic practice.…”
Section: Prospectsmentioning
confidence: 99%